2007
DOI: 10.1007/s11606-007-0455-2
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and Communication in the Health Care Setting: Experiences of Older Vietnamese Immigrants, A Qualitative Study

Abstract: BACKGROUND: As patients grow older, accurate communication with health care providers about cancer becomes increasingly important. However, little is known about the cancer communication experiences of older Asian immigrants. OBJECTIVE:To learn about the cancer-related communication experiences of older Vietnamese immigrants from the insider perspective. DESIGN:Qualitative study (grounded theory, constant comparative method) using individual interviews with older Vietnamese immigrants with the purpose of discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 13 publications
2
54
0
Order By: Relevance
“…19 Discussion of screening for CRC is complicated and time consuming, and may be omitted or abbreviated when there are language barriers. 22 A recent study showed that patients who spoke Spanish at home were less likely to receive CRC screening compared to patients who spoke English at home, even after controlling for English proficiency and patient characteristics.…”
Section: Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…19 Discussion of screening for CRC is complicated and time consuming, and may be omitted or abbreviated when there are language barriers. 22 A recent study showed that patients who spoke Spanish at home were less likely to receive CRC screening compared to patients who spoke English at home, even after controlling for English proficiency and patient characteristics.…”
Section: Objectivementioning
confidence: 99%
“…18 Communication problems when discussing cancer screening are also documented with VietnameseAmericans. 19 Furthermore, there is evidence that fewer providers discuss CRC screening with non-English speaking patients 20 even when translators are available. 21 …”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest migrant patients are more passive during medical consultations, ask fewer questions and have less understanding of cancer and treatment than non-migrants [2,5,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…And indeed this expectation is borne out in the extant literature. In studies on the patient's perspective, the salient finding has been that these participants adopt an inhibited, compliant attitude towards those who are charged with treating them (Fancher et al, 2010;Nguyen et al, 2007;Tran, 2009).…”
Section: Introductionmentioning
confidence: 99%